The Discounted Money Value of Human Life Losses Associated With COVID-19 in Mauritius - Laurent Musango; Ajoy Nundoochan; Joses Muthuri Kirigia (Frontiers Media S.A., 2020)
Background: Mauritius along with other 12 countries in the African Region was identified at the early start of the COVID-19 pandemic as being at high risk due to high volume of international travel, high prevalence of non-communicable diseases and co-morbidities, high population density and significant share of population over 60 years (16%). The objective of this study was to estimate the total discounted money value of human life losses (TDMVCLMAURITIUS) associated with COVID-19 in Mauritius.Methods: The human capital approach (HCA) was used to estimate the TDMVCLMAURITIUS of the 10 human life losses linked with COVID-19 in Mauritius as of 16 October 2020. The HCA model was estimated with the national life expectancy of 75.51 years and a discount rate of 3%. A sensitivity analysis was performed assuming (a) 5 and 10% discount rates, and (b) the average world life expectancy of 73.2 years, and the world highest life expectancy of 88.17 years.Results: The money value of human lives lost to COVID-19, at a discounted rate of 3%, had an estimated TDMVCLMAURITIUS of Int$ 3,120,689, and an average of Int$ 312,069 per human life lost. Approximately 74% of the TDMVCLMAURITIUS accrued to persons aged between 20 and 59 years. Reanalysis of the model with 5 and 10% discount rates, holding national life expectancy constant, reduced the TDMVCLMAURITIUS by 19.0 and 45.5%, respectively. Application of the average world life expectancy at 3% discount rate reduced TDMVCLMAURITIUS by 13%; and use of the world highest life expectancy at 3% discount rate increased TDMVCLMAURITIUS by 50%.Conclusions: The average discounted money value per human life loss associated with COVID-19 is 12-fold the per capita GDP for Mauritius. All measures implemented to prevent widespread community transmission of COVID-19 may have saved the country 837 human lives worth Int$258,080,991. This evidence, conjointly with human rights arguments, calls for increased investments to bridge the existing gaps for achieving universal health coverage by 2030.